The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.3329/jbau.v9i2.11046
|View full text |Cite
|
Sign up to set email alerts
|

Landing centers and availability of fish species in fish markets of Mymensingh town

Abstract: An investigation was carried out on fish landing centers, fish markets and fish fauna of the Mymensingh town to   overview the location of the fish landing/entering centers, the source of supply and availability of fisheries organisms   in Mymensingh town. The investigation was conducted from October 2009 to September 2010 in sixteen landing   centers and markets of Mymensingh town. Among a total of 122 species of fishes were available of which, 113 were   finfish and 9 were shellfish. Out of 113 finfish, 85 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…Hilsha and Bagda chingri were leading position from marine and brakish water species. These findings are much convenient with Chandra et al [25] where they observed 99 freshwater fish species and 14 marine fish species in the 16 fish markets and five important fish landing centers of Mymensingh districts.…”
Section: Resultssupporting
confidence: 80%
“…Hilsha and Bagda chingri were leading position from marine and brakish water species. These findings are much convenient with Chandra et al [25] where they observed 99 freshwater fish species and 14 marine fish species in the 16 fish markets and five important fish landing centers of Mymensingh districts.…”
Section: Resultssupporting
confidence: 80%
“…The helminthic parasites were identified morphologically and parasitologically using standard identification keys and pictorial guides [14][15][16][17][18].…”
Section: Identification Of Parasitesmentioning
confidence: 99%
“…The parasites were again washed with 70% alcohol, temporarily mounted in Canada balsam on slides, and finally examined under a compound microscope (BX51, Olympus, Japan) and identified according to Chandra (2004). The prevalence, abundance, and mean density of parasites were estimated according to Margolis et al (1982).…”
Section: Methodsmentioning
confidence: 99%